A Study of the Strategic Positioning for the Singapore Medical Tourism Industry - Sultana, Mahanaaz (2010)
Medical Tourism is a global industry with different countries competing on price or on quality. Every successful medical tourism destination possesses certain factors – either inherent or acquired, that place its healthcare industry in a competitive advantage vs. others in the industry. Singapore is one such nation whose healthcare industry has been successful in attracting thousands of international patients every year; this despite the extremely small size of the country and a relatively higher cost of operations. To understand the drivers behind this success and ultimately the competitive advantage of the Singapore medical tourism industry, I have performed a detailed SWOT Analysis not only for Singapore but also for the major competitor nations. This was followed by a detailed Michael Porter’s Value Chain Analysis for the Singapore medical tourism industry. The analysis revealed that Singapore has been following a quality focused differential pricing strategy of strategically positioning its medical tourism industry. This is evident from a strong focus on quality across the value chain right from the fact that all major hospitals are JCI accredited to the high quality of service delivery by the ancillary industries – hotels and transportation. For the promotion of the industry Singapore Government plays a critical role – directly through an integrated promotion strategy and indirectly though providing a safe, secure and clean environment and a government machinery that is efficient, transparent and corruption free. The support that the Singapore medical tourism industry receives from the government is conspicuous by its absence in other major competitor countries, hence providing a significant source of competitive advantage that is difficult for others to replicate. However, Singapore medical tourism industry cannot rest on its laurels. Competitors across the globe are trying to emulate the Singapore strategy making it essential for Singapore to focus its attention on being one step ahead to sustain its current position and grow within its premium pricing category. My analysis suggests that the long term sustenance of the differential pricing strategy of the Singapore medical tourism industry is only feasible if it focuses on creating expertise in a limited number of critical medical procedures supported by a quality service delivery for other procedures.